Guidelines for Authors Version 2012 - Geográfica, Perspectiva (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Perspectiva Geográfica is a magazine specializing in geographic studies and spatial planning, aimed at academic communities, research and territorial development issues interested in geography and related sciences, which publishes original and unpublished scientific and technological research, reflection and revie warticles, referring to the spatiality of social, economic, political, cultural and natural phenomena, from various perspectives and theoretical approaches. This publication also welcomes studies on technical and methodological aspects of the work of geographers and applied geography work in the fields of geomatics and spatial planning and research frontier, which result in the development of geographical science.